2014
DOI: 10.2147/ijnrd.s72011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating targets and costs of treatment for secondary hyperparathyroidism in incident dialysis patients: the FARO-2 study

Abstract: BackgroundThe aim of this analysis was to estimate biochemical parameters and the costs of treatment of secondary hyperparathyroidism (SHPT) in a subpopulation of the FARO-2 study.MethodsThe FARO-2 observational study aimed at evaluating the patterns of treatment for SHPT in naïve hemodialysis patients. Data related to pharmacological treatments and biochemical parameters (parathyroid hormone [PTH], calcium, phosphate) were recorded at entry to hemodialysis (baseline) and 6 months later (second survey). The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the United States, IV vitamin D became the primary route of administration for management of secondary hyperparathyroidism in patients receiving maintenance dialysis after reports that, in contrast to oral administration, IV administration was associated with fewer episodes of hypercalcemia and hyperphosphatemia, better adherence, and improved bone outcomes (1,2). Other studies evaluating the efficacy of oral versus IV vitamin D examined primarily short-term treatment effects and found no differences in iPTH levels (1,4,5,7,8). A recent study examined the efficacy and safety of patients on maintenance hemodialysis previously receiving IV paricalcitol who then switched to oral calcitriol (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, IV vitamin D became the primary route of administration for management of secondary hyperparathyroidism in patients receiving maintenance dialysis after reports that, in contrast to oral administration, IV administration was associated with fewer episodes of hypercalcemia and hyperphosphatemia, better adherence, and improved bone outcomes (1,2). Other studies evaluating the efficacy of oral versus IV vitamin D examined primarily short-term treatment effects and found no differences in iPTH levels (1,4,5,7,8). A recent study examined the efficacy and safety of patients on maintenance hemodialysis previously receiving IV paricalcitol who then switched to oral calcitriol (9).…”
Section: Discussionmentioning
confidence: 99%
“…At 5 months, the mineral and bone disorder parameters were comparable with levels that had been achieved before the switch. Finally, some longer-term studies have suggested that parenteral therapies were associated with improved outcomes (1,7,8). Limitations of past studies included small sample sizes, short-term follow-up, and importantly, inclusion of patients who at baseline were already being treated differently.…”
Section: Discussionmentioning
confidence: 99%
“…There is little published data looking at the efficacy and tolerability of oral calcitriol in the calcimimetic era to manage secondary hyperparathyroidism in hemodialysis patients and no information regarding real practice-based experience of such a treatment regimen in a US dialysis center setting. A study in Italy, focusing on management of secondary hyperparathyroidism in incident hemodialysis patients found little to no differences (including no cost differences) between 105 patients using oral calcitriol compared to 33 patients using intravenous paracalcitiol, but found that intravenous paracalcitol had slightly increased the percentage of patients at KDOQI targets at 6 months follow up (16). In our study, there were no significant differences in percentage of patients achieving KDOQI targets pre and post-conversion.…”
Section: Discussionmentioning
confidence: 99%
“…As described elsewhere [29][30][31][32], the FARO study was a prospective multicenter survey that evaluated treatment practices in 28 dialysis centers in Italy from April 2006 to October 2007; during the study, data on secondary hyperparathyroidism (SHPT) management and alignment with Kidney Disease Outcomes Quality Initiative (KDOQI) target ranges from all patients receiving HD were recorded. The FARO-2 study [33][34][35] was designed to integrate the data of the Table 1. Sources for hospitalizations causes, reimbursement tariffs, and number of hospitalizations in Italy (2008) Causes of hospitalizations (as reported in the FARO-2 study)…”
Section: Methodsmentioning
confidence: 99%